The efficacy of trimethoprim-sulfamethoxazole treatment in children with acute bloody diarrhea - Selvi Nafianti; Oke R. Ramayani; Dedy G. Daulay; Supriatmo Supriatmo; Berlian Hasibuan; Atan B. Sinuhaji (Indonesian Pediatric Society, 2007)
Background The etiologies of bloody diarrhea are shigella,amoeba, enterocolitis, trichuriasis, and other causes i.e, EIEC,Campylobacter jejuni or rotavirus. In developing countries,trimetroprim-sulfamethoxazole (TMP-SMP) is effective in 80%of children with bloody diarrhea.Objective To determine the efficacy of trimethoprim-sulfa-methoxazole (TMP-SMX) treatment in children with acute bloodydiarrhea.Methods A randomized double blind clinical trial was conductedin Adam Malik Hospital and Dr. Pirngadi Hospital Medan duringSeptember 2003-March 2004. Children aged 2-24 months oldwith diagnosis of acute bloody diarrhea were randomized into twogroups to either receive TMP-SMX or placebo for 5 days.Microscopic fecal analysis was performed on the first, second,fifth and twelfth day, and the results were compared.Results A total of 68 children consisted of 48 (71%) boys and 20(29%) girls were enrolled. Each group had 34 participants.Analysis of the first day showed leukocyte and erythrocyte in thestool specimens, which were all absent on the twelfth day in bothgroups. There was no difference in stool analysis between TMP-SMX and placebo group in day two (P=0.758), day five (P=0.341)and day twelve. Diarrhea duration in TMP-SMX and placebogroup was 7.18 days and 6.65 days, respectively. This differentwas statistically not significant (P=0.385).Conclusion There is no difference in the efficacy of trimethoprim-sulfamethoxazole treatment compared to placebo in children withacute bloody diarrhea.